Application of Scout Extracurricular Activities to Students' Social Values at SD Negeri 1 Lambheu, Aceh Besar District - Nur, Muhammad; Ahadin, Ahadin; Husin, M. (Elementary Education Research, 2023)
The purpose of this study was to find out the application of scout extracurricular activities to the social values of students at SD Negeri 1 Lambheu. This study used a qualitative approach with a descriptive research type. The research subjects were 1 school principal and 1 Scoutmaster at SD Negeri 1 Lambheu, Aceh Besar District. Data collection techniques through observation, interviews and documentation. Based on the results of data analysis, from data reduction, data collection and drawing conclusions, based on the description of the research results at SD Negeri 1 Lambheu and discussion of ethical values in scout extracurricular activities at SD Negeri 1 Lambheu, researchers can draw conclusions about the values -the social values of students in Scout extracurricular activities at SD Negeri 1 Lambheu, including: (1) Discipline, (2) Independence, (3) Cooperation, (4) love of the motherland, (5) Responsibility, (6) Please help , (7) Religious, (8) Honesty and (9) Tolerance